i-Tasmik mobile platform – enabling tahfiz student to memorize Al-Quran independently - Musa, Muhammad Ghufran; Yusop, Mohd Hamzi Niyaz; Mohd Sopee, Muhammad Mustaqeem; Mohamad Ali, Noor Azian (IEEE, 2018)
This paper proposes a conceptual solution to assist Tahfiz student on practicing memorizing Al-Quran easily and independently. This also will help Madrasah Tahfiz to monitor their students when they went back home and for long distance student. i-Tasmik is a mobile application adopting a freemium business model which aim to provide a platform for Madrasah Tahfiz student, Ustaz and Ustazah to help enhance their Al-Quran memorization. It also has a function for Madrasah and ustaz/ustazah to monitor their students’ performance. This platform uses a voice recognition system. Nine blocks of Business Model Canvas (BMC) framework, value proposition design (VPD) and environmental map have been used as the methodologies for this paper.